Advancing health care information system for enhanced sharing: project report - Krishnasamy, Jayasri (My University, 2015)
During Summer 2003, I worked as an intern at the Community Health Council, a not-for-profit health information organization serving the health care system of northeastern Kansas. Their current major goal is to help health care providers share vital information. This is made possible by creating automated information warehouses and mining systems, and having the providers use that system. This exercise will also ensure the creation of secured systems that comply with the Health Insurance Portability and Accountability Act of 1996.
Sponsored by the Marjorie J. and Richard L.D. Morse Family and Community Public Policy Scholarship
Citation: Krishnasamy, J. (2003). Advancing health care information system for enhanced sharing: project report. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: Information storage and retrieval systems--Medical care; Medical informatics; Health services administration--Computer networks; Reports; Reports